2021
DOI: 10.1111/nmo.14278
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disordered eating in adults with gastrointestinal disorders: A systematic review

Abstract: Background Patients with gastrointestinal disorders are prone to heightened awareness of dietary intake. When diet‐related thoughts or behaviors are excessive, they may lead to psychological distress, nutritional compromise, and impair medical treatment. Identification of disordered eating behavior and eating disorders is crucial for effective management, but data on their prevalence within this population remain scarce. We conducted a systematic review of the prevalence of disordered eating behavior and eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 74 publications
(231 reference statements)
2
28
0
1
Order By: Relevance
“…Burton Murray et al reported 40% of DGBI patients had ARFID, with the most frequent presentation being fear of adverse consequences 19 . The systematic review by Peters et al reported disordered eating in 13%–55% of patients with gastrointestinal disorders, with highest prevalence in those with DGBI 20 . Given these findings, it is likely that orthorexia is common in this patient group, although this was not directly examined in these studies.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Burton Murray et al reported 40% of DGBI patients had ARFID, with the most frequent presentation being fear of adverse consequences 19 . The systematic review by Peters et al reported disordered eating in 13%–55% of patients with gastrointestinal disorders, with highest prevalence in those with DGBI 20 . Given these findings, it is likely that orthorexia is common in this patient group, although this was not directly examined in these studies.…”
Section: Introductionmentioning
confidence: 87%
“…19 The systematic review by Peters et al reported disordered eating in 13%-55% of patients with gastrointestinal disorders, with highest prevalence in those with DGBI. 20 Given these findings, it is likely that orthorexia is common in this patient group, although this was not directly examined in these studies. These data, while focusing on other forms of ED, are hypothesis-generating that use of dietary therapies may also lead to increased orthorexic behaviors.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In active IBD, gut symptoms are often associated with food intake, leading to restrictive eating behaviour. Disordered eating behaviour is more prevalent in patients with IBD than in the general population and persistent abnormal food intake, especially in the absence of active disease, should alert the clinician to a possible eating disorder 18 19…”
Section: Introductionmentioning
confidence: 99%